Catechol-substituted siderophore colistin exhibits superior antimicrobial activity than its unmodified polypeptide counterpart - Sara Bescós-Ramo; Enrique Gámez; María del Mar Encabo-Berzosa; Milagros Piñol; Luis Oriol; Manuel Arruebo (BMC Chemistry)
Abstract Catechol moieties have been covalently coupled to the last-resort polypeptide antibiotic colistin via esterification and amidation reactions, inspired by the superior antimicrobial action of cefiderocol, i.e., a catechol-substituted siderophore cephalosporin. Among the tested strategies, the incorporation of the catechol motif by amidation reduces by 50% the minimum concentration to inhibit the growth of a clinical strain of uropathogenic Escherichia coli (E. coli) in its planktonic form. Its minimum bactericidal concentration is reduced by 25% after chemical modification. The tested modified antibiotic did not show cytotoxicity against human fibroblasts and keratinocytes at bactericidal doses. Additionally, due to the potential nephrotoxicity of colistin, the cytotoxicity of this catechol-substituted siderophore colistin was evaluated in a 3D model of human renal organoids showing no cytotoxicity at the doses tested. The chemical incorporation of catechol groups to existing antibiotics can reduce the doses to exert a fast antimicrobial action reducing the chances to develop antibiotic resistance.